Assessment of Errors in Handwritten Prescriptions in Zliten City- Libya - Alhmmali Abdalla; Aimen Heshad; Nour Aldeen Ehmedh; Mohammed Gratem (AlQalam Journal of Medical and Applied Sciences, 2024)
Errors in handwritten prescriptions are a major factor in medical errors and are the main cause of harm to patients due to the lack of clarity of the prescription or the lack of correct data, which leads to the prescription of the wrong medication, causing adverse events. The present study aimed to identify the common errors in handwriting prescriptions in Zliten City. To collect information about errors in handwritten prescriptions, we used two models: first, we distributed fifty-one questionnaires to fifty-one pharmacies distributed in all areas of Zliten city, and second, we collected one hundred and fifty prescriptions from different health facilities distributed in different areas within Zliten city. The questionnaires and prescriptions then analysed to identify medical errors. In the first model of the questionnaire, the results are as follows: the patient’s name and age are often present, while the gender, doctor’s name, and stamp are often absent. The main issue lies in the clarity of the font for the drug’s name, dose, and dosage form. In the second model of the prescriptions, the results are as follows: the patient’s name is mostly present, while gender and diagnosis are absent in about 40% of the prescriptions, the doctor’s name is mostly absent, and only 2% of the prescriptions have the doctor’s stamp and number in the syndicate, and the main issue lies in the clarity of the font for the drug’s name, dose, and dosage form., as it is unclear in between 20-30% of the prescriptions. We found that the patient’s information is present in most prescriptions the opposite of the questionnaire in which it is less. Also in the prescriber’s information, the analysis in our result for prescription contradicted the questionnaires, as most prescribers in the questionnaire are present, we also found that during the analysis of drug information in prescription not clear more than in the questionnaire. From this research, we concluded that there are many errors in prescriptions, possibly because of the large number of cases that need to be seen by the doctor and the speed of writing, and perhaps because doctors forget the vocabulary of the names of medicines. Because of the many errors in handwritten prescriptions, we must immediately switch to computerized prescription writing. تعد الأخطاء في الوصفات الطبية المكتوبة بخط اليد عاملاً رئيسيًا في الأخطاء الطبية وهي السبب الرئيسي في إلحاق الضرر بالمرضى بسبب عدم وضوح الوصفة الطبية أو عدم وجود بيانات صحيحة، مما يؤدي إلى وصف الدواء الخطأ، مما يتسبب في حدوث أحداث سلبية. هدفت الدراسة الحالية إلى تحديد الأخطاء الشائعة في الوصفات الطبية المكتوبة بخط اليد في مدينة زليتن. لجمع المعلومات حول الأخطاء في الوصفات الطبية المكتوبة بخط اليد، استخدمنا نموذجين: أولاً، قمنا بتوزيع واحد وخمسين استبيانًا على واحد وخمسين صيدلية موزعة في جميع مناطق مدينة زليتن، وثانيًا، قمنا بجمع مائة وخمسين وصفة طبية من مرافق صحية مختلفة موزعة في مناطق مختلفة داخل مدينة زليتن. ثم تم تحليل الاستبيانات والوصفات الطبية لتحديد الأخطاء الطبية. في النموذج الأول من الاستبيان كانت النتائج كالتالي: اسم المريض وعمره غالبا موجودين بينما الجنس واسم الطبيب والختم غالبا ما يكون غائبا، والمشكلة الرئيسية تكمن في وضوح الخط الخاص باسم الدواء والجرعة وشكل الجرعة، وفي النموذج الثاني من الوصفات الطبية كانت النتائج كالتالي: اسم المريض موجود في الغالب بينما الجنس والتشخيص غائبان في حوالي 40% من الوصفات الطبية، اسم الطبيب غائب في الغالب، و2% فقط من الوصفات الطبية تحمل ختم الطبيب ورقم النقابة، والمشكلة الرئيسية تكمن في وضوح الخط الخاص باسم الدواء والجرعة وشكل الجرعة، حيث أنه غير واضح في ما بين 20-30% من الوصفات الطبية، وجدنا أن معلومات المريض موجودة في معظم الوصفات الطبية على عكس الاستبيان الذي تكون فيه أقل. كذلك في معلومات الطبيب المعالج، تناقضت نتائج التحليل في نتيجتنا للوصفات الطبية مع الاستبيانات، حيث أن أغلب الأطباء المعالجين في الاستبيانات حاضرون، كما وجدنا أنه أثناء تحليل معلومات الأدوية في الوصفات الطبية لم تكن واضحة أكثر من الاستبيان. ومن هذا البحث استنتجنا أن هناك أخطاء كثيرة في الوصفات الطبية، ربما بسبب كثرة الحالات التي تحتاج إلى مراجعة الطبيب وسرعة الكتابة، وربما لأن الأطباء ينسون مفردات أسماء الأدوية. وبسبب كثرة الأخطاء في الوصفات الطبية المكتوبة بخط اليد، يجب أن ننتقل فورًا إلى كتابة الوصفات الطبية بالكمبيوتر